2011
DOI: 10.1002/jbmr.491
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of fracture pathogenesis in urban South African children: The birth to twenty cohort

Abstract: South African black children fracture less than white children. Differences in bone mass, body composition, and physical activity may be contributing risk factors. This study aimed to investigate the association between fracture prevalence, bone mass, and physical activity in South African children. Using the Bone Health cohort of the Birth to Twenty longitudinal study, we retrospectively obtained information of lifetime fractures until age 15 years in 533 subjects. Whole-body bone mineral content (BMC), bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
7
2
Order By: Relevance
“…However, in our earlier study of the Bt20 cohort [30], we did not find an inverse association between fracture history prevalence and bone mass at two time points during childhood and adolescence. In fact, in white males, there was a positive association between fracture risk and bone mass [30], possibly associated with increased contact sport participation [19]. Thus, the association between maternal LS BMC and adolescent fracture risk might be a proxy for structural differences in the adolescents, with low maternal BMC indicating poorer adolescent bone strength rather than differences in bone mass per se.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…However, in our earlier study of the Bt20 cohort [30], we did not find an inverse association between fracture history prevalence and bone mass at two time points during childhood and adolescence. In fact, in white males, there was a positive association between fracture risk and bone mass [30], possibly associated with increased contact sport participation [19]. Thus, the association between maternal LS BMC and adolescent fracture risk might be a proxy for structural differences in the adolescents, with low maternal BMC indicating poorer adolescent bone strength rather than differences in bone mass per se.…”
Section: Discussioncontrasting
confidence: 85%
“…Intuitively, this association should not be surprising as several studies, although not all [2528], have shown that children who had fracture(s) tend to have reduced BMC and BA compared to their peers who had no fractures, and genetic inheritance (maternal and paternal bone mass) plays a large role in determining childhood BMC, BA and peak bone mass [29]. However, in our earlier study of the Bt20 cohort [30], we did not find an inverse association between fracture history prevalence and bone mass at two time points during childhood and adolescence. In fact, in white males, there was a positive association between fracture risk and bone mass [30], possibly associated with increased contact sport participation [19].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results differ from those reported for African-American and non-black children in the USA, where African-American children have greater bone area and BMC at all measured sites (lumbar spine, hip, radius, and whole body) than non-black children [48]. In South Africa, despite the lower calcium intakes and the poorer growth of black children, they have a fracture incidence approximately half that of white children even though X-ray absorptiometry-measured bone mass is similar at most skeletal sites [51]. …”
Section: Bone Mass In Children Living In Developing Countriessupporting
confidence: 38%
“…A study of English children (3, 4) suggested a higher fracture rate in whites compared with non-whites, although statistical significance was not established. A study of South African children found the rate of fractures for white children to be almost twice that of children of African ancestry (5, 6). The purpose of this prospective, multi-center study was to examine race/ethnicity as a risk factor for fracture in a large, diverse cohort of children and adolescents from different regions across the United States (U.S.).…”
mentioning
confidence: 99%